2019
DOI: 10.1002/hbm.24791
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine effects on default mode network activity and vigilance: A randomized, placebo‐controlled crossover simultaneous fMRI/EEG study

Abstract: In resting‐state functional connectivity experiments, a steady state (of consciousness) is commonly supposed. However, recent research has shown that the resting state is a rather dynamic than a steady state. In particular, changes of vigilance appear to play a prominent role. Accordingly, it is critical to assess the state of vigilance when conducting pharmacodynamic studies with resting‐state functional magnetic resonance imaging (fMRI) using drugs that are known to affect vigilance such as (subanesthetic) k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 66 publications
5
32
0
Order By: Relevance
“…NMDA antagonist evoked increases in HFO activity in nucleus accumbens have previously be shown to be reduced by clozapine (Hunt et al, 2015). The ketamine-induced power changes in β -power and γ-power observed here and in other preclinical studies (Phillips et al, 2012) have been recapitulated in humans (Muthukumaraswamy et al, 2015) and correlated with fMRI connectivity changes (Zacharias et al, 2020). However, HFO activity has not yet been reported in humans.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…NMDA antagonist evoked increases in HFO activity in nucleus accumbens have previously be shown to be reduced by clozapine (Hunt et al, 2015). The ketamine-induced power changes in β -power and γ-power observed here and in other preclinical studies (Phillips et al, 2012) have been recapitulated in humans (Muthukumaraswamy et al, 2015) and correlated with fMRI connectivity changes (Zacharias et al, 2020). However, HFO activity has not yet been reported in humans.…”
Section: Discussionsupporting
confidence: 57%
“…Complementary to this approach, a deeper understanding of the central effects of xanomeline could be obtained by profiling its effect on inter-regional fMRI synchronization, or "functional connectivity", in distributed brain circuits via resting-state fMRI (rsfMRI) (Errico et al, 2015;Gozzi and Schwarz, 2016). In addition, oxygen (O 2 ) amperometry provides a complementary probe-based method to measure the local hemodynamic response in conscious mobile animals (Lowry et al, 1997;Li et al, 2016), and quantitative electro-encephalography (qEEG) provides a means of monitoring the power-frequency profile of the brain's electrical rhythms more directly, unfiltered by the hemodynamic response underlying the fMRI signals (Ye et al, 2018;Zacharias et al, 2020). Given the established role of cholinergic systems in arousal and neocortical excitation, cholinergic modulation could conceivably also affect large-scale cortical coupling and electrical activity of the brain, resulting in rsfMRI-and qEEG-detectable effects.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the substantial number of studies focused on ketamine‐induced brain alterations in patients with unipolar depression (Chen et al., 2019; McMillan et al., 2019; Morris et al., 2020; Nugent et al., 2019; Zacharias et al., 2020), only a few studies have investigated the functional brain alterations associated with ketamine augmentation in patients with TRBPD. Recently, Diazgranados et al conducted a 2‐week study to investigate the antidepressant effects of ketamine infusions in patients with TRBPD and found that 71% of patients with TRBPD responded to ketamine augmentation (Diazgranados et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the substantial number of studies focused on ketamine-induced brain alterations in patients with unipolar depression (Chen et al, 2019;McMillan et al, 2019;Morris et al, 2020;Nugent et al, 2019;Zacharias et al, 2020), only a few studies have investigated the functional brain alterations associated with ketamine augmentation in patients with TRBPD.…”
Section: Introductionmentioning
confidence: 99%
“…The significant heterogeneity in the literature is therefore not surprising. With regard to healthy volunteers (HVs), some studies that used resting-state fMRI to examine ketamine's acute effects found primarily increased connectivity (4-7), others reported mainly reductions (8)(9)(10), and some reported patterns of increases and decreases in connectivity depending on the brain region examined (11)(12)(13)(14). Studies of functional connectivity between one hour and 24 h post-infusion have produced similarly heterogeneous results (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%